Light in the Trees - Folkins, Gail Louise, 1963- (Book collections on Project MUSE., 2016)
""A memoir about growing up in a mountain foothill in Washington state, chronically a coming of age for author and region. Includes further views of the Northwest through the eyes of Southwest terrain and climate."--Provided by publisher"--